ART in Europe, 2016: results generated from European registries by ESHRE. Issue 3 (31st July 2020) - ,; Wyns, C; Bergh, C; Calhaz-Jorge, C; De Geyter, Ch; Kupka, M S; Motrenko, T; Rugescu, I; Smeenk, J; Tandler-Schneider, A; Vidakovic, S; Goossens, V
Abstract: STUDY QUESTION: What are the reported data on cycles in ART, IUI and fertility preservation (FP) interventions in 2016 as compared to previous years, as well as the main trends over the years? SUMMARY ANSWER: The 20th ESHRE report on ART and IUI shows a progressive increase in reported treatment cycle numbers in Europe, with a decrease in the number of transfers with more than one embryo causing a reduction of multiple delivery rates (DR), as well as higher pregnancy rates and DR after frozen embryo replacement (FER) compared to fresh IVF and ICSI cycles, while the outcomes for IUI cycles remained stable. WHAT IS KNOWN ALREADY: Since 1997, ART aggregated data generated by national registries, clinics or professional societies have been collected, analysed by the European IVF-monitoring Consortium (EIM) and reported in 19 manuscripts published in Human Reproduction and Human Reproduction Open . STUDY DESIGN, SIZE, DURATION: Yearly collection of European medically assisted reproduction (MAR) data by EIM for ESHRE. The data on treatments performed between 1 January and 31 December 2016 in 40 European countries were provided by either National Registries or registries based on personal initiatives of medical associations and scientific organizations. PARTICIPANTS/MATERIALS, SETTING, METHODS: In all, 1347 clinics offering ART services in 40 countries reported a total of 918 159 treatment cycles, involving 156 002 with IVF, 407 222 with ICSI, 248 407 with FER, 27 069 with preimplantation genetic testing, 73 927 with egg donation (ED), 654 with IVM of oocytes and 4878 cycles with frozen oocyte replacement (FOR). European data on IUI using husband/partner's semen (IUI-H) and donor semen (IUI-D) were reported from 1197 institutions offering IUI in 29 and 24 countries, respectively. A total of 162 948 treatments with IUI-H and 50 467 treatments with IUI-D were included. A total of 13 689 FP interventions from 11 countries including oocyte, ovarian tissue, semen and testicular tissue banking in pre-and postpubertal patients were reported. MAIN RESULTS AND THE ROLE OF CHANCE: In 20 countries (18 in 2015) with a total population of approximately 325 million inhabitants, in which all ART clinics reported to the registry, a total of 461 401 treatment cycles were performed, corresponding to a mean of 1410 cycles per million inhabitants (range 82–3088 per million inhabitants). In the 40 reporting countries, after IVF the clinical pregnancy rates (PR) per aspiration and per transfer in 2016 were similar to those observed in 2015 (28.0% and 34.8% vs 28.5% and 34.6%, respectively). After ICSI, the corresponding rates were also similar to those achieved in 2015 (25% and 33.2% vs 26.2% and 33.2%). After FER with own embryos, the PR per thawing is still on the rise, from 29.2% in 2015 to 30.9% in 2016. After ED, the PR per fresh embryo transfer was 49.4% (49.6% in 2015) and per FOR 43.6% (43.4% in 2015). In IVF and ICSI together, the trend towards the transfer of fewer embryos continues with the transfer of 1, 2, 3 and ≥4 embryos in 41.5%, 51.9%, 6.2% and 0.4% of all treatments, respectively (corresponding to 37.7%, 53.9%, 7.9% and 0.5% in 2015). This resulted in a proportion of singleton, twin and triplet DRs of 84.8%, 14.9% and 0.3%, respectively (compared to 83.1%, 16.5% and 0.4%, respectively in 2015). Treatments with FER in 2016 resulted in twin and triplet DR of 11.9% and 0.2%, respectively (vs 12.3% and 0.3% in 2015). After IUI, the DRs remained similar at 8.9% after IUI-H (7.8% in 2015) and at 12.4% after IUI-D (12.0% in 2015). Twin and triplet DRs after IUI-H were 8.8% and 0.3%, respectively (in 2015: 8.9% and 0.5%) and 7.7% and 0.4% after IUI-D (in 2015: 7.3% and 0.6%). The majority of FP interventions included the cryopreservation of ejaculated sperm ( n = 7877 from 11 countries) and of oocytes ( n = 4907 from eight countries). LIMITATIONS, REASONS FOR CAUTION: As the methods of data collection and levels of completeness of reported data vary among European countries, the results should be interpreted with caution. A number of countries failed to provide adequate data about the number of initiated cycles and deliveries. WIDER IMPLICATIONS OF THE FINDINGS: The 20th ESHRE report on ART and IUI shows a continuous increase of reported treatment numbers and MAR-derived livebirths in Europe. Being already the largest data collection on MAR in Europe, continuous efforts to stimulate data collection and reporting strive for future quality control of the data, transparency and vigilance in the field of reproductive medicine. STUDY FUNDING/COMPETING INTEREST(S): The study has no external funding and all costs were covered by ESHRE. There are no competing interests.